Experience With Ventriculoperitoneal and Lumboperitoneal Shunting for the Treatment of Idiopathic Intracranial Hypertension: A Single Institution Series. Issue 2 (22nd April 2021) - Sweid, Ahmad; Daou, Badih J; Weinberg, Joshua H; Starke, Robert M; Sergott, Robert C; Schaefer, Joseph; Hauge, Julie; Elizabeth, Caroline; Chalouhi, Nohra; Gooch, Reid; Herial, Nabeel; Zarzour, Hekmat; et al.
Abstract: BACKGROUND: CSF shunting is among the most widely utilized interventions in patients with idiopathic intracranial hypertension (IIH). Ventriculoperitoneal shunting (VPS) and lumboperitoneal shunting (LPS) are 2 possible treatment modalities. OBJECTIVE: To evaluate and compare complications, malfunction, infection, and revision rates associated with VPS compared to LPS. METHODS: Electronic medical records were reviewed to identify baseline and treatment characteristics for patients diagnosed with IIH treated with VPS or LPS. RESULTS: A total of 163 patients treated with either VPS (74.2%) or LPS (25.8%) were identified. The mean follow-up was 35 mo. Shunt revision was required in 40.9% of patients. There was a nonsignificant higher rate of revision with LPS (52.4%) than VPS (36.4%, P  = .07). In multivariate analysis, increasing patient age was associated with higher odds of shunt revision ( P  = .04). LPS had higher odds of shunt revision, yet this association was not significant ( P  = .06). Shunt malfunction was the main indication for revision occurring in 32.7%, with a significantly higher rate with LPS than VPS ( P  = .03). In total, 15 patients had shunt infection (9.4% VPS vs 12.2% LPS P  = .50). The only significant predictor of procedural infection was the increasing number of revisions ( P  = .02). CONCLUSION: The incidence of shunt revision was 40.9%, with increasing patient age as the sole predictor of shunt revision. The incidence of shunt malfunction was significantly higher in patients undergoing LPS, while there was no significant difference in the incidence of shunt infection between the 2 modalities.